Bioactive Metabolites in Melaleuca leucadendra Leaves Extract: Phytochemical Profilling and GC-MS Characterization for Antimicrobial Relevance - Royani, Idha; Setiabudidaya, Dedi; Miksusanti, Miksusanti; Arsyad, Fitri Suryani; Atina; Assaidah (Chempublish Journal, 2026)
The global escalation of antimicrobial resistance (AMR) necessitates the exploration of natural sources of antibacterial agents. This study examined the ethanolic leaf extract of Melaleuca leucadendra's phytochemical composition, chemical profile, and antibacterial activity. Alkaloids, flavonoids, saponins, tannins, phenolics, terpenoids, and steroids were all detected by phytochemical screening. The quantitative total flavonoid content (TFC) of the extract was 17.78 mg QE/g, while the total phenolic content (TPC) was 292.43 mg GAE/g extract. Gas Chromatography–Mass Spectrometry (GC–MS) analysis identified oxygenated esters (18.86%), oxygenated aromatics (15.22%), phenolic derivatives (13.44%), and flavonoids (12.86%), methoxylated aromatics and terpenoids (5.34%), phytol, and fatty acid derivatives. These metabolite classes are widely reported to exert antibacterial effects through multiple mechanisms such as membrane disruption, enzyme inactivation, and inhibition of nucleic acid synthesis. Antibacterial testing against Staphylococcus aureus and Escherichia coli using the agar diffusion method showed a concentration-dependent response, with the highest activity at 80% extract (15.67 ± 0.58 mm and 15.33 ± 0.58 mm inhibition zones, respectively). Raman spectroscopy confirmed the interaction between polymer molecules and secondary metabolite compounds in the extract, thereby potentially enhancing antibacterial properties. These findings highlight that the antibacterial activity of M. leucadendra is mediated by the synergistic interplay of phenolics, flavonoids, methoxylated aromatics, terpenoids, and fatty acids. The findings offer compelling proof that M. leucadendra is a viable natural source for the creation of antibacterial compounds that will lessen antibiotic resistance.